A multi-facets ontology matching approach for generating PLC domain knowledge graphs. Issue 2 (2020) - An, Yameng; Qin, Feiwei; Sun, Danfeng; Wu, Huifeng
Abstract: Programmable Logic Controller (PLC) has been playing an important role in industrial automation. Users want to improve programming efficiency by implementing code reuse and more intelligent code retrieval. Due to the heterogeneity of different PLC development environments, it is then necessary to design a computable knowledge model to semantically represent, organize, and utilize these diversified resources. Using the ontology technique is a common way to achieve the interoperability of heterogeneous systems. Aiming at this, we propose an ontology matching approach in this paper. Knowledge extraction and alignment are difficult for most of the knowledge graphs construction tasks, however, we are able to build the PLC domain knowledge graph with high accuracy and completeness by considering PLC domain characteristics, designing layered ontology, and implementing the matching process primarily on schema level instead of instance level.